Effect of selenium on methimazole-induced liver damage and oxidative stress in adult rats and their offspring. (August 2014) - Sefi, Mediha; Amara, Ibtissem Ben; Troudi, Afef; Soudani, Nejla; Hakim, Ahmed; Zeghal, Khaled Mounir; Boudawara, Tahia; Zeghal, Najiba
This study aimed to investigate the protective effect of selenium (Se) on methimazole (MMI; an antithyroid drug)-induced hepatotoxicity in adult rats and their progeny. Female Wistar rats were randomly divided into four groups of six rats in each group: group I served as controls that received standard diet; group II received MMI in drinking water as 250 mg L −1 and standard diet; group III received both MMI (250 mg L −1, orally) and Se (0.5 mg kg −1 of diet); group IV received Se (0.5 mg kg −1 of diet) as sodium selenite. Treatments were started from the 14th day of pregnancy until day 14 after delivery. Exposure of rats to MMI promoted oxidative stress with an increase in liver malondialdehyde levels, advanced oxidation protein products and protein carbonyl contents and a decrease in the levels of glutathione, nonprotein thiols and vitamin C. A decrease in the activities of liver glutathione peroxidase, superoxide dismutase, catalase and lactate dehydrogenase and in the levels of plasma total protein and albumin was also observed. Plasma transaminase activities and total, direct and indirect bilirubin levels increased. Coadministration of Se through diet improved all biochemical parameters. The histopathological changes confirmed the biochemical results. Therefore, our investigation revealed that Se, a trace element with antioxidant properties, was effective in preventing MMI-induced liver damage.